Physical Medicine and Rehabilitation Role of Complete Recovery after Intracerebral Hemorrhage in Eclampsia with HELLP Syndrome: A Rare Case - Tambunan, Tresia Fransiska Ulianna; Putri, Yoan Utami; Utami, Diniah; Chandra Kasih, Siti Aminah; Ulfa, Meryta; Kurnain, Dave Nicander (Faculty of Medicine, Universitas Airlangga, 2025)
Cerebrovascular accident during hypertensive disorder of pregnancy is a rare condition, but carries high risk of mortality and morbidity due to its unpredictable onset. Intracerebral Hemorrhage (ICH) associated with eclampsia is responsible for 5–12% of maternal deaths during pregnancy. Eclampsia is defined as a convulsive episode occurring in the setting of preeclampsia. The hallmark presentation of eclampsia is characterized with generalized tonic-clonic seizures which typically lasted 60 to 90 second in duration, might be preceded with headaches, visual disturbance, abdominal pain, and increased blood pressure. HELLP syndrome frequently associated with severe preeclampsia-eclampsia and is characterized by three hallmark features of hemolysis, elevated liver enzymes, and low platelets. Here, we report an unusual case of 25-year-old primigravida with 38 weeks gestation, which developed sudden eclampsia and intracranial hemorrhage. A night before admission, she complained about headache and had projectile vomit in the morning that followed by generalized seizure. She had no history of seizure or high blood pressure during her antenatal care. Laboratory test shows elevated liver enzyme and low platelets count and CT-scan which showed hemorrhage in left intraparenchymal lobes. She was successfully managed by multidisciplinary approach including emergency cesarean section, conservative neurological treatment for intraventricular hemorrhage and rehabilitation ever since in intensive care unit until discharge from ward. Rehabilitation approach in eclampsia with superimposed intraparenchymal hemorrhages could start safely as early as possible by collaboration with other departments. This can help mother achieved independency of activity daily living and improvement of cardiorespiratory endurance as before.